PROTOTIPE KEAMANAN PINTU GESER OTOMATIS MENGGUNAKAN FINGERPRINT BERBASIS ARDUINO - Rasyid, Abdul; Purwanto, Timur Dali (Rang Teknik Journal, 2025)
Fingerprint identification technology is a security technology that has a high level of security. Fingerprints are one of everyone's personal data, where this data will not be the same from one another. By using fingerprints as a key to a security system, only certain people can access a system, so automatically other people who are not registered cannot access it. In this final project, an automatic sliding door lock has been designed that uses fingerprint detection as the security of this door. Fingerprint scanning will be done by the fingerprint module which will then be matched with templates that have been stored in the database. If there is a match, the fingerprint module will send data to the microcontroller and can open and close the door automatically. This final project has resulted in automatic sliding door security that can provide a high level of security by using fingerprints as security at certain times so that unregistered people cannot access them. With the percentage of workability from ten experiments, that is, when the condition of the finger is dry, the tool can work 100%, when the condition is humid, the tool can work 100%, and the condition of the finger there are small scratches, the tool can still work 70%, While in wet conditions the tool is difficult to detect fingerprints with the percentage of the tool can work as much as 30%.Keywords: automatic door lock, fingerprint, fingerprint module, security, microcontroller